2019
DOI: 10.1136/annrheumdis-2019-216227
|View full text |Cite
|
Sign up to set email alerts
|

High genetic risk score is associated with early disease onset, damage accrual and decreased survival in systemic lupus erythematosus

Abstract: ObjectivesTo investigate associations between a high genetic disease risk and disease severity in patients with systemic lupus erythematosus (SLE).MethodsPatients with SLE (n=1001, discovery cohort and n=5524, replication cohort) and healthy controls (n=2802 and n=9859) were genotyped using a 200K Immunochip single nucleotide polymorphism array. A genetic risk score (GRS) was assigned to each individual based on 57 SLE risk loci.ResultsSLE was more prevalent in the high, compared with the low, GRS-quartile (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
79
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 46 publications
5
79
1
1
Order By: Relevance
“…Recently, a Swedish group found that a higher cumulative genetic risk score spanning 57 SLE-associated loci was implicated in SLE onset, severity, organ damage, and death; however, APOL1 was not identi ed likely due to a lack of patients with African continental ancestry (38). The current study highlights the need to perform additional genetic susceptibility analyses in SLE patients of diverse ancestral backgrounds.…”
Section: Apol1 Genotype Is Associated With Case Fatalitymentioning
confidence: 76%
See 1 more Smart Citation
“…Recently, a Swedish group found that a higher cumulative genetic risk score spanning 57 SLE-associated loci was implicated in SLE onset, severity, organ damage, and death; however, APOL1 was not identi ed likely due to a lack of patients with African continental ancestry (38). The current study highlights the need to perform additional genetic susceptibility analyses in SLE patients of diverse ancestral backgrounds.…”
Section: Apol1 Genotype Is Associated With Case Fatalitymentioning
confidence: 76%
“…SLE is an extremely heterogeneous disease, with variation in clinical manifestations, race and ethnicity, disease onset, medication requirements, and disease activity all contributing to morbidity and mortality (24,36,37). Genetic susceptibility to early damage accrual, particularly in renal and cardiovascular domains, is implicated in early SLE deaths (38).…”
Section: Apol1 Genotype Is Associated With Case Fatalitymentioning
confidence: 99%
“…In this gene–environment interaction study of SLE risk, the largest conducted to date and the first, to our knowledge, to employ GWAS results rather than to investigate individual candidate polymorphisms, we created an updated, weighted GRS based on existing GRS studies of SLE (28,29), and tested for interactions between SLE genetic factors and smoking status in relation to their potential influence on SLE risk. We found that having a high wGRS and being a current or recent smoker were each individually strongly associated with SLE risk: each standard deviation increase in the wGRS more than doubled the risk of SLE, while current smokers and those who had recently quit smoking had an increased SLE risk of ~50% compared to never and more distant past smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the GRS (genetic risk score) has been widely adopted to predict disease outcomes from genetic variants [66]. The previous studies in SLE showed that overall mortality was higher in the striking GRS SLE patients; also, the high cumulative genetic risk could predict the speci c organ damages such as proliferative nephritis and cardiovascular disease [67].…”
Section: Discussionmentioning
confidence: 99%